Genomic and Phytochemical Assessment of Chavir (Ferulago angulata) under Different in vitro Conditions - Lia Shooshtary; Mansour Omidi; Ardeshir Qaderi; Amir Reza Zare Karizi; Ali Mehrafarin (Institue of Medicinal Plants, ACECR, 2018)
Background:Ferulago Angulata (Known in Iran as Chavir) is  an endangered species and belongto Apiaceae family with Anti fugal and anti-bacterial activity that can act as a natural preservator. Objective: The present study was done to evaluate the effect of in vitro culture conditions and plant growth regulators on somaclonal variation and the phytochemical content of in vitro regenerated plants. Methods: After the callus induction phase, the calli were transferred to Murashige and Skoog(MS) medium supplemented with 1-Naphthaleneacetic acid(NAA) and 6-Benzylaminopurine (BAP) for regeneration stage. The essential oils were extracted by Clevenger apparatus and the yield and composition of essential oils were assayed by GC/Mass. The genomic DNA was isolated from in vitro regenerated plants by CTAB method. Inter-Simple Sequence Repeat (ISSR), Start codon Targeted (SCoT) and CAAT Box Derived Polymorphism (CBDP) molecular markers were used to assess the effect of plant growth regulators on somaclonal variation. Results: The highest percentage of callus formation (100%) was obtained via radicle explant in MS medium supplemented with 2 mg/L 2,4-D and 1mg/L BAP. Also, maximum percentage of regeneration was occurred via derived calli from hypocotyl in MS medium supplemented with 0.1 mg/L BAP and 0.5 NAA. The phytochemical assay revealed a considerable differences between natural habitats and invitro regenerated plants. For example the percentage of α-Pinene in plants derived from natural habitats and invitro conditions were 27 and 1.53 respectively. The yield of essential oils were 2.26 and 0.64 (ml/100g D.M.) in natural habitats and invitro regenerated plants respectively. The result of PCR assay and differences of banding patterns, indicated genetic variation between tissue cultured samples. Conclusion: The results indicated that invitro culture conditions had a considerable effect on genome and metabolome   of Ferulago angulate.